تحديد الحجم الامثل لمجموعة الحبوب والخضراوات والفاكهة في ليبيا خلال الفترة (1990-2010) - هاجر حسين محمد; نجاح عبدالرحيم مفتاح; ربيعة خالد خليفة محمد (Scientific Journal of University of Benghazi, 2017)
The problem of research is that domestic production is unable to meet the growing needs of domestic demand and the corresponding increase in population growth rates. The actual grain production in Libya was estimated at 231.27 thousand tons during the period 1990-2010, Which is about 2.3%. This increase is offset by an increase in consumption, as actual production does not cover all the needs. Consumption is therefore covered by importing grain from abroad. It was also found that vegetables during the period referred to in Libya increased at a CAGR of 17%. This increase was offset by an increase in consumption. The optimum volume of vegetable production obtained from available for actual consumption in Libya was estimated using the Nerlov model which amounted to 856.0 000 tons, that is, Libya is achieving large quantities of domestic production and therefore Libya imports only a small amount of vegetables from abroad. The study also showed that the average production of fruit in Libya reached about 493.48 thousand tons during the same period, and this production is decreasing at a CAGR of about 9% on the average, ie Libya does not rely on its consumption of fruit on local production, but imports the rest of its fruit from The exterior is special that cannot be grown like bananas and other kinds of fruits.